The influence of iodine on the Antarctic stratospheric ozone hole - Cuevas, Carlos A.; Fernandez, R.P.; Kinnison, Douglas E.; Li, Qinyi; Lamarque, Jean-François; Trabelsi, T.; Francisco, J.S.; Solomon, S.; Saiz-Lopez, A. (Proceedings of the National Academy of Sciences, 2022)
10 pags., 6 figs., 2 tabs. The catalytic depletion of Antarctic stratospheric ozone is linked to anthropogenic emissions of chlorine and bromine. Despite its larger ozone-depleting efficiency, the contribution of oceanemitted iodine to ozone hole chemistry has not been evaluated, due to the negligible iodine levels previously reported to reach the stratosphere. Based on the recently observed range (0.77 ± 0.1 parts per trillion by volume [pptv]) of stratospheric iodine injection, we use the Whole Atmosphere Community Climate Model to assess the role of iodine in the formation and recent past evolution of the Antarctic ozone hole. Our 1980-2015 simulations indicate that iodine can significantly impact the lower part of the Antarctic ozone hole, contributing, on average, 10% of the lower stratospheric ozone loss during spring (up to 4.2% of the total stratospheric column). We find that the inclusion of iodine advances the beginning and delays the closure stages of the ozone hole by 3 d to 5 d, increasing its area and mass deficit by 11% and 20%, respectively. Despite being present in much smaller amounts, and due to faster gas-phase photochemical reactivation, iodine can dominate (∼73%) the halogen-mediated lower stratospheric ozone loss during summer and early fall, when the heterogeneous reactivation of inorganic chlorine and bromine reservoirs is reduced. The stratospheric ozone destruction caused by 0.77 pptv of iodine over Antarctica is equivalent to that of 3.1 (4.6) pptv of biogenic very short-lived bromocarbons during spring (rest of sunlit period). The relative contribution of iodine to future stratospheric ozone loss is likely to increase as anthropogenic chlorine and bromine emissions decline following the Montreal Protocol. This study received funding from the European Research Council Executive Agency under the European Union’s Horizon 2020 Research and Innovation Programme (Project ERC-2016-COG 726349 CLIMAHAL). D.E.K. is partly supported by NASA Grant 80NSSC19K0952. S.S. is partly supported by ...